Early-onset coronary atherosclerosis in patients with low levels of omega-3 fatty acids - Bittner, D. O.; Göller, Markus; Zopf, Yurdagül; Achenbach, Stephan; Marwan, Mohamed (European Journal of Clinical Nutrition, 2020)
Objectives: Coronary artery calcification (CAC) can reliably predict cardiovascular events. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are thought to inhibit vascular calcification on a cellular level and in animal models, however, the correlation in humans is controversial. Methods: In symptomatic patients, CAC was quantified according to Agatstons’ method using non-contrast coronary CT. We assessed the association of EPA and DHA with early-onset coronary atherosclerosis, defined as presence of CAC above the 75th Agatston-Score (AS) percentile in sex adjusted age categories. Erythrocyte fatty acid composition was analyzed with a standardized methodology. The percentage of EPA and DHA in relation to all fatty acids present in the erythrocyte membrane is regarded the Omega-3 Index®. Results: Among 71 patients, 51 were below and 20 were above the 75th AS-percentile. No differences were seen in age, gender, cardiovascular risk factors, and relevant medication. In univariable analysis, significantly lower values for EPA (0.77%[0.63; 0.97] vs. 0.93%[0.72; 1.21]; p = 0.045), DHA (4.90%[4.12; 5.57] vs. 5.50%[4.58; 6.52]; p = 0.038) and the Omega-3 Index (5.73%[4.75; 6.35] vs. 6.22%[5.46; 7.71]; p = 0.034) were seen in patients above the 75th AS-percentile. All other fatty acids showed no significant differences. In multivariable analysis, the Omega-3 Index showed a significant inverse association with early onset of CAC (OR: 0.533 (95%CI: 0.303–0.938; p = 0.029)), independent of age, gender, statin use, and creatinine level (all p > 0.05). Conclusions: Low levels of EPA and DHA (Omega-3 Index) are associated with early-onset coronary atherosclerosis. This finding needs to be validated in larger cohorts and might help understand the beneficial cardiovascular effects of omega-3 fatty acids.
CRIS-Team Scopus Importer:2020-01-21